Risk Analysis In Viet Nam Hardware Sector And Policies During And After The Global Crisis - PhD, Trung Van Dinh; (corresponding), To Hien Tha, PhD, Asso.Prof; PhD, Nguyen Huynh Dang Khoa (Migration Letters, 2024)
The aim of this study is to present Risk Analysis in Viet Nam Hardware Sector and Policies During and After The Global Crisis. Until now, with uncertainty or risks, we change various scenarios of fin.leverage (Fl) to see beta values sensitivity. Authors use in this study method of analysis (scenario of fin leverage) and beta value estimation and also correlation b.t them. In our sample size with twenty two firms in computer sector - hardware: with live data we analyze beta values sensitive to fin leverage (or decrease). Also fin leverage has correlated negatively with mean values (equity beta) (0,742, 0,715 and 0,716). Hence, We also analyze that in this study when leverage is going to increase up to 30%, the risk dispersion level increases little less as well as the asset beta var, compared to the case it is going to decrease down to 20%.